A Crustal Control on the Fe Isotope Systematics of Volcanic Arcs Revealed in Plutonic Xenoliths From the Lesser Antilles - Cooper, G. F.; Inglis, E. C. (Frontiers in Earth Science, 2022)
Lavas produced at subduction zones represent the integration of both source heterogeneity and an array of crustal processes, such as: differentiation; mixing; homogenisation; assimilation. Therefore, unravelling the relative contribution of the sub-arc mantle source versus these crustal processes is difficult when using the amalgamated end products in isolation. In contrast, plutonic xenoliths provide a complementary record of the deeper roots of the magmatic plumbing system and provide a unique record of the true chemical diversity of arc crust. Here, we present the δ56Fe record from well characterised plutonic xenoliths from two distinct volcanic centres in the Lesser Antilles volcanic arc–the islands of Martinique and Statia. The primary objective of this study is to test if the Fe isotope systematics of arc lavas are controlled by sub-arc mantle inputs or during subsequent differentiation processes during a magma’s journey through volcanic arc crust. The Fe isotopic record, coupled to petrology, trace element chemistry and radiogenic isotopes of plutonic xenoliths from the two islands reveal a hidden crustal reservoir of heavy Fe that previously hasn’t been considered. Iron isotopes are decoupled from radiogenic isotopes, suggesting that crustal and/or sediment assimilation does not control the Fe systematics of arc magmas. In contrast to arc lavas, the cumulates from both islands record MORB-like δ56Fe values. In Statia, δ56Fe decreases with major and trace element indicators of differentiation (SiO2, Na2O + K2O, Eu/Eu*, Dy/Yb), consistent with fractionating mineral assemblages along a line of liquid descent. In Martinique, δ56Fe shows no clear relationship with most indicators of differentiation (apart from Dy/Yb), suggesting that the δ56Fe signature of the plutonic xenoliths has been overprinted by later stage processes, such as percolating reactive melts. Together, these data suggest that magmatic processes within the sub-arc crust overprint any source variation of the sub-arc mantle and that a light Fe source is not a requirement to produce the light Fe isotopic compositions recorded in volcanic arc lavas. Therefore, whenever possible, the complimentary plutonic record should be considered in isotopic studies to understand the relative control of the mantle source versus magmatic processes in the crust.